Born by the war - V. . Polkanov (Высшее образование в России)
The article traces the history of Omsk State Technical University on the basis of archival documents. The ancestor of Omsk machine-building institute (further Omsk Polytechnical Institute, Omsk State Technical University) was Voroshilovgrad (Lugansk) evening machine-building institute, which was relocated from Ukraine to Omsk at the beginning of the Great Patriotic War. The article draws attention to the biographies of the first professors who became the backbone of the further teaching staff of Omsk State Machine-building Institute.